Employee engagement and open service innovation: The roles of creative self-efficacy and employee innovative behaviour - Wan, Xiaole; He, Ruixin; Zhang, Guixian; Zhou, Jian (Frontiers in Psychology, 2022)
In a rapidly changing and highly uncertain business environment, how to make organizations gain innovation kinetic energy and enhance organizational innovative ability has always been a popular topic in management research. In this paper, creative self-efficacy and employee innovative behaviour are taken as continuous intermediaries to explore the mechanism of employee engagement in open service innovation. Taking employees of several tourism enterprises as samples, 103 valid questionnaires are tested empirically. The results show that (a) employee engagement can promote open service innovation, (b) creative self-efficacy plays a complete intermediary role between employee engagement and employee innovative behaviour, (c) creative self-efficacy and employee innovative behaviour play a continuous mediating role in the relationship between employee engagement and open service innovation, and (d) by constructing the support vector regression model, the open service innovation prediction model is further verified. The research results clarify the mechanism from individual behaviour to organizational innovation, which is of great practical value to help enterprise open service innovation.